Relationship between Growth Hormone Level and Growth Parameters among Primary School Students with Malocclusion in Center of the Middle city of Iraq - Hawraa Abdulla Spahi; Shaymaa Shaker Taha; Samaneh Razeghi (Migration Letters, 2023)
Background: Growth hormone (GH) is a critical regu-lator of the growth process in children. Malocclusion is a dento-skeletal disorder that may affect the function and aesthetics of patients and thereby cause impairments in their quality of life and social interactions. The relation-ship among malocclusion, body mass index (BMI), and GH level in children is debatable. Aim of the study: This study aimed to assess the relation of GH levels to mal-occlusion and growth parameters among a group of primary school students. Subjects and Methods: A cross-sectional comparative study was performed among school children aged 10–11 years in the center of Kerbala City, Iraq. Only 88 students were randomly selected to test the relationship between GH and BMI. ELISA was applied to examine salivary samples to estimate the GH levels. The presence of malocclusion was detected through intraoral examination in accordance with angle classification. Overjet and overbite were measured by the dental caliper Vernier. The growth parameters for BMI (height and weight ) were analyzed. Results: This study showed a high prevalence of overweight females over males. No relationship was found between demographic variables and BMI. Low levels of GH were reported in overweight patients. Class I malocclusion was higher than class II in all BMI categories. Increased overjet and overbite were mostly higher than normal in the BMI categories. The presence of posterior crossbite was higher in normal BMI, whereas obesity was the least. All these results showed no significant association between overbite and BMI. Conclusion: An inversely propor-tional relationship exists between basal metabolic rate and GH levels among school children.